Características hídricas, fisiológicas e nutricionais afetadas pela aplicação de remineralizador na cultura do milho em dois solos - Fernandes, Marco Iony dos Santos (2025)
Brazilian soils have low fertility, requiring the use of soil amendments, high doses of fertilizers and corn cultivars appropriate to the production system to achieve high yields. To reduce dependence on fertilizers, remineralizers have emerged as regional alternatives, which can improve the chemical, physical and biological characteristics of soils. This study aimed to investigate the effect of the use of soil remineralizers on soil water storage, gas exchange, xylem water potential, their influence on cationic relations and corn productivity in different soils and levels of potassium (K) stress, in addition to evaluating their effect on different corn hybrids for height, stalk diameter, dry mass, thousand-seed weight (PMS) and productivity. The results indicate that the use of the remineralizer promoted improvements in soil water storage, dry matter content, gas exchange and xylem water potential, in addition to increasing the K, Ca and Mg contents in the soil and leaves, improving cationic relations, favoring productivity especially under moderate K stress. When evaluated together with corn hybrids, the best results are observed especially in Latosol, regardless of the corn hybrid, and the AS1820 hybrid stood out in stem diameter, dry mass, PMS and productivity, with no difference for height. However, the interaction between hybrids, soils and remineralizers is complex, requiring further research for a deeper understanding.